2021
DOI: 10.3390/su13105576
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Taguchi Method for Optimizing the Process Parameters of Producing Controlled Low-Strength Materials by Using Dimension Stone Sludge and Lightweight Aggregates

Abstract: In view of the increasing concerns over non-renewable resource depletion and waste management, this paper studied the development of low-density controlled low-strength material (CLSM) by using stone sludge and lightweight aggregates. First, the investigation was performed at a laboratory scale to assess the effects of the composition on the properties of the resulting low-density CLSM. The Taguchi method with an L9(34) orthogonal array and four controllable three-level factors (i.e., the stone sludge dosage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The optimum combination is determined based on the signalto-noise ratio (S/N) and is used to understand the effects of each parameter on the responses. Several studies have been conducted using the Taguchi method to convert complex waste compositions into construction materials [32,35,36]. The Taguchi method is efficiently utilized for examining waste materials with complex compositions, but its disadvantage is that it can only be used to optimize a single objective.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum combination is determined based on the signalto-noise ratio (S/N) and is used to understand the effects of each parameter on the responses. Several studies have been conducted using the Taguchi method to convert complex waste compositions into construction materials [32,35,36]. The Taguchi method is efficiently utilized for examining waste materials with complex compositions, but its disadvantage is that it can only be used to optimize a single objective.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the portion larger than 40 mm was removed after MSWI screening and then heat treated at 900 • C. The results showed that the addition of MSWI bottom ash improved the compressive strength of the CLSM sample, and the leachable substances exerted no harm on health and the environment [21]. Other solid waste for the preparation of CLSM includes soft shale from coal mine overburden [22], dimension stone sludge [23], cement kiln dust [24], waterworks sludge [25], waste glass powder [26], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The dosage of a certain material cannot be adjusted independently without affecting the mixing ratio, so its mixing ratio is generally obtained by changing the ratio recommended in ACI 229R by trial and error [1]. The experimental design of this trial-anderror method has contingency and limitations, while the orthogonal experimental design can explain the influence of different experimental factors alone or synergistically through fewer experiments, which greatly reduces the experimental workload and improves the work efficiency [23]. For instance, Wang and colleagues explored the optimum ratio of the filler material with fly ash, desulfurization gypsum, and coal gangue as the main components through orthogonal experiments and found that the content of the cementitious material mainly composed of fly ash was the primary factor affecting the strength [7].…”
Section: Introductionmentioning
confidence: 99%
“…Taguchi method is mainly in the parameter design stage based on assessing the influence of factors on the objective function, thereby determining the optimal parameters. Taguchi method is commonly used in many fields such as using experimental design, using for optimal design, using for quality control, using economic analysis [19][20][21][22][23]. The Taguchi method has the advantage of being simple, with a small number of trials, and can be quantitative or qualitative.…”
Section: Introductionmentioning
confidence: 99%